Secondary prevention of acute venous thrombosis. Modern trends - V. Y. Bogachev; B. V. Boldin; O. V. Dzhenina; V. N. Lobanov (Амбулаторная хирургия)
Venous thromboembolic complications (VTC) including deep veins thrombosis and pulmonary artery thromboembolia are sufficiently frequent but preventable states. In industrially developed countries 1-2 cases of VTC per 1 thousand persons per year are registered. In USA 900 thousand patients suffer from VTC annually. But these figures are most likely conservative as due to diffuseness of a clinical pattern and insufficient sensitivity of screening tests the frequency of verified VTC doesn't exceed 60-70% [1, 2].